2017
DOI: 10.1159/000477589
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Thrombectomy for Middle Cerebral Artery Division Occlusions: A Systematic Review and Meta-Analysis

Abstract: Background: Middle cerebral artery division (M2) occlusion was significantly underrepresented in recent mechanical thrombectomy (MT) randomized controlled trials, and the approach to this disease remains heterogeneous. Objective: To conduct a systematic review and meta-analysis of outcomes at 90 days among patients undergoing MT for M2 middle cerebral artery (MCA) occlusions. Methods: Five clinical databases were searched from inception through September 2016. Observational studies reporting 90-day modified Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The estimated incidence of M2 occlusions in the population is 7 per 100 000, with M2 segment strokes accounting for approximately 4.2% of all AIS . Multiple studies and registries have attempted to explore outcomes in patients with M2 and M3 occlusions treated with ECR . To date, no randomised control studies have been published for this M2/M3 subgroup, however, as described below, retrospective studies demonstrated efficacy of treatment with good recanalisation rates and good patient outcomes comparable to many studies investigating ECR in more proximal occlusions.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated incidence of M2 occlusions in the population is 7 per 100 000, with M2 segment strokes accounting for approximately 4.2% of all AIS . Multiple studies and registries have attempted to explore outcomes in patients with M2 and M3 occlusions treated with ECR . To date, no randomised control studies have been published for this M2/M3 subgroup, however, as described below, retrospective studies demonstrated efficacy of treatment with good recanalisation rates and good patient outcomes comparable to many studies investigating ECR in more proximal occlusions.…”
Section: Introductionmentioning
confidence: 99%
“…7,9,10,15 A recent subanalysis from the ARISE II trial (Analysis of Revascularization in Ischemic Stroke With EmboTrap) showed no difference in rates of reperfusion (92.1% versus 91.2%, P=1.0), good outcome (70.2% versus 69.7%, P=0.946), and mortality (6.6% versus 10.5%, P=0.37) in M1 versus M2 patients, respectively 7. The MR CLEAN Registry reported data from 244 M2 MT and 759 M1 sICH Although we found no difference in rates of good functional outcomes in M1 and M2 patients, M2 patients in STRATIS had a significantly higher rate of sICH (4% versus 1%, P=0.01).…”
mentioning
confidence: 99%
“…6 Data on M2 occlusions in the United States is limited to small cohorts and several meta-analyses which demonstrated the safety and feasibility of MT. [5][6][7][8][9][10][11] The recent American Heart Association guidelines for early management of acute ischemic stroke acknowledged this paucity of data and recommended treatment in carefully selected patients within the first 6 hours from symptoms onset. 12 Moreover, the time to treatment effect in association with functional outcomes remains unknown in this population.…”
mentioning
confidence: 99%
“…20 MT was suggested to provide similar safe access with high recanalization rates and functional independence between MeVO, which is mainly M2 occlusion, and LVO of M1. [4][5][6]21 Conversely, the tendency for an increased risk of symptomatic hemorrhage had been controversial. 22,23 Based on these circumstances, we focused on MeVO with thrombus migration after MT and reported the outcomes of intraarterial UK.…”
Section: Discussionmentioning
confidence: 99%
“…MT for acute ischemic stroke with medium vessel occlusion (MeVO) was reported to be angiographically effective and safe. [4][5][6] The patient status and vessel condition in MeVO with thrombus migration are different from those in direct MeVO. Moreover, the role of MT for MeVO after LVO remains unclear.…”
Section: Introductionmentioning
confidence: 99%